Electronic dictionary classification as problem of modern computer lexicography - Купріянов, Євген Валерійович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2015)
The present article is devoted to electronic dictionary typology classification with regard to the recent developments in modern computer lexicography. The notion electronic dictionary is defined and its main signs to be taken in account for elaboration of dictionary classification. The classifications of national and foreign researchers are considered and their main disadvantages are revealed. The author’s own classification of electronic dictionary is offered and parameters to be used while carrying out this classification